The Effect of Business Risk and Dividend Policy on Financial Performance with Capital Structure as an Intervening Variable: Pengaruh Risiko Bisnis dan Kebijakan Dividen Terhadap Kinerja Keuangan dengan Struktur Modal Sebagai Variabel Intervening - Wiguna, Rr Hentia Endang Rahayu; Sriyono, Sriyono (Indonesian Journal of Innovation Studies, 2022)
This study aims to determine the effect of business risk and dividend policy on financial performance with capital structure as an intervening variable. This study uses quantitative methods with secondary data as a data source. In this study the population data used are all pharmaceutical companies listed on the Indonesia Stock Exchange. The observation period was from the 2014-2020 period. In this study, non-probability sampling technique used in this study is purposive sampling. There are 8 pharmaceutical companies used as samples in this study. The data analysis technique used in this research is Structural Equation Modeling Partial Least Square (SEM-PLS). The results of this study indicate that business risk has an effect on financial performance. Dividend Policy Affects Financial Performance. Business risk Affects Capital Structure. Dividend Policy Affects Capital Structure. Capital Structure Affects Financial Performance. Capital Structure Mediates the Impact of Business Risk on Financial Performance. Capital Structure Mediates the Effect of Dividend Policy on Financial Performance